Medical Tourism and the Best Interests of the Critically ill Child in the Era of Healthcare Globalisation - Bhatia, Neera (Med Law Rev, 2020)
In this article, we examine emerging challenges to medical law arising from healthcare globalisation concerning disputes between parents and healthcare professionals in the care and treatment of critically ill children. We explore a series of issues emerging in English case law concerning children’s medical treatment that are signs of increasing globalisation. We argue that these interrelated issues present distinct challenges to healthcare economics, clinical practice, and the operation of the law. First, social media leverages the emotive aspects of cases; secondly, the Internet provides unfiltered information about novel treatments and access to crowdfunding to pay for them. Finally, the removal of barriers to global trade and travel allows child medical tourism to emerge as the nexus of these issues. These aspects of globalisation have implications for medicine and the law, yet child medical tourism has been little examined. We argue that it affects a range of interests, including children’s rights, parents’ rights as consumers, and the interests of society in communalised healthcare. Identifying putative solutions and a research agenda around these issues is important. While cases involving critically ill children are complex and emotionally fraught, the interconnectedness of these issues requires the law to engage and respond coherently to the impacts of healthcare globalisation.